Science teasers - Wyler, Rose.; Baird, Eva Lee. (New York : Harper & Row, 1966)
Concerned with basic science this is a collection of explanations, puzzles, and experiments, that include space puzzles; tricks magicians use, teasers concerning weight, and balance; conclusions that seem logical, and puzzles that are good parlor tricks.
Include index.
Keywords: Scientific recreations -- Juvenile literature; Science -- Experiments -- Juvenile literature; Magic tricks -- Juvenile literature